Re-making anevalution of gold ore deposits the blakeshale series of Complexgold-platinum mineralization; Abstract of Internal conference on Fundamental and Applied Problems - Korobeinikov A. F. Alexander Feopenovich (1995, 1995)
В фонде НТБ ТПУ отсутствует